Yang Fana Ditelan oleh Hidup: Sebuah Usulan Model Tubuh Kebangkitan Orang Percaya - Manurung, Philip (Veritas : Jurnal Teologi dan Pelayanan, 2023)
The doctrine of the Resurrection Body often causes difficulties and confusion for Christians. Some available models tend to be speculative with many possible constructs. This study aims to clear up this confusion by reviewing the doctrine of humanity according to the Reformed tradition, as well as the incarnation and resurrection of Christ, to produce a model of biblical and complete eschatological resurrection body of believers. This study shows that the pattern of pneumasomatic unity in the anthropotheistic integrative nature is manifested from the creation of man, the birth of Christ, up until His ascension to heaven. Like Jesus, at the time of the resurrection, the recreated body of believers is swallowed up by the life-giving Spirit. These findings are compared with the resurrection body model of “psychosomatic unity inducing the Holy Spirit” by Aphrahat and the “pneumatic body one with Christ” model by Troels Engberg-Pedersen.